Reinterpreting Democracy Through Zizioulas Ontology of Personhood - Indraswara, Angga (P3TK, Sanata Dharma University, 2018)
In the landscape of modern theology, John D. Zizioulas is noted for his contribution in retrieving the works of the Cappadocian Fathers in the areas of Trinitarian theology and ontology of personhood. Disenchanted by the predominance of Augustinian Substantialism, which he claims to place too much emphasis on the unity of God, Zizioulas turns to the ideas of the Cappadocian Fathers in order to offer a Personalist approach in Trinitarian theology. Such an approach, in turn, leads to the development of a particular ontology of personhood, in which Person is understood both as hypostasis and ekstasis. This article appropriates Zizioulas conception of person to provide an ontological justification for the idea of democracy. Zizioulas conception of Person as hypostasis can form the ontological ground for the notion of equality, whereas his idea of Person as ekstasis offers the ground for the cultivation of a democratic political culture, in which communion with the Poor and Suffering Other is not simply a theological possibility, but a civic duty.